Identification, Integration, and Mainstreaming FSF into National FSN Strategy Promoting Agriculture Diversification Towards Zero Hunger: A Situation Overview and Way Forward to Empirical Research - Oo, Khin Mar (2018)
Khin Mar Oo IFPRI-FAO conference side event, "Accelerating the End of Hunger and Malnutrition" November 28–30, 2018 Bangkok, Thailand